Vermicomposting influences phosphorus microbiology leading to phosphorus enrichment in end product. (2nd December 2010) - Saha, N.; Chattrejee, Pranab; Sharma, A.; Metiya, G.; Halder, M.; Mukherjee, D.
The investigation reveals the relative efficacy of composting techniques regarding phosphorus transformation of rice straw (RS) and water-hyacinth (WH). The recipe for each substrate: cow-dung:soil:FYM was in the ratio of 6:3:0.5:0.5. Vermicomposting of WH resulted in the highest proliferation of phosphate solubilising microorganisms (PSM) and their solubilising capacity (PSC) besides causing the maximum phosphatases activities, total and water soluble phosphorus (WSP) in addition to the lowest C:P ratio. Heap method was less effective than vermicomposting. Vermicomposting enhanced 10.6, 9.4 and 28.6% for total, WSP and PSC, respectively, over heap method as well as 26.2, 28.6 and 79.3%, respectively, over pit method. WH effectuated an increase of 17.2, 17.7, 16.2% for total, WSP and PSC, respectively over RS composting. The results, thus, indicate the superiority of WH vermicomposting for phosphorus enrichment in compost.